Piezo-electrical control of gyration dynamics of magnetic vortices - Filianina, Mariia; Baldrati, L.; Hajiri, Tetsuya; Litzius, Kai; Foerster, Michael; Aballe, Lucia; Klaeui, M. (Applied Physics Letters, 2019)
In this work, we first statically image the electrically controlled magnetostatic configuration of magnetic vortex states and then we dynamically image the time-resolved vortex core gyration tuned by electric fields. We demonstrate the manipulation of the vortex core gyration orbit by engineering the magnetic anisotropies. We achieve this by electric fields in a synthetic heterostructure consisting of a piezoelement coupled with magnetostrictive microstructures, where the magnetic anisotropy can be controlled by strain. We directly show the strong impact of the tailored anisotropy on the static shape of the vortex state and the dynamic vortex core orbit. The results demonstrate the possibility of using electric field induced strain as a low-power approach to tune the dynamical response of magnetic vortices.
CRIS-Team Scopus Importer:2023-03-27